Historical references on the presence Of Omani travellers In Malaysia - Ahmad H.Osman, Rahmah; Nadri, Muhammad Nabil; Alzeheimi, Saleh; Wan Fazli, Wan Norizzati; Yaapar, Md. Salleh; Mansor Majdin, Mohamad Firdaus (Siauliai University, 2022)
This study demonstrates that both the nations of Malaysia and Oman were historically interconnected via the Indo-Pacific maritime route since the olden days. Classical Arab literatures as written by various famous historians or sea travellers from as early as the Abbasid Period from the 9th century CE up until around its demise in the 13th century CE presented various accounts pertaining the presence of Omanis from the Persian Gulf visiting what is today part of Malaysia. Likewise, they also appeared in a few classic Malaysian literatures, especially during the advent of the early modern period in between the 18th to 19th century CE when historical writing became a more established and well-preserved activity in Malay Archipelago. All references shared rather similar settings, although some of them appeared to be divided apart for centuries long. The activities of Omani travellers back then seemed to have concentrated in the northern Malaysian state, which then was known as the powerful kingdom (later sultanate) of Kedah. Since its days, were incorporated within the thalassocracy of the famous Srivijayan Empire (Ar. Zabaj or Mulku Jawah) around 8th century CE until the arrival of the European colonialism in 18th century CE, Kedah was a natural international maritime hub which had attracted travellers from both East and West including the Omanis.